Proposta metodológica para análises de obras literárias através da Linguística de Corpus: o caso de Paulo Coelho - Rangel, Marden Aleandro (2022)
This research aimed to develop a methodological proposal capable of analyzing literary works through Corpus Linguistics. Our main intention was to promote a union between Linguistics and Literature, using tools capable of verifying lexical and stylistic aspects of one or more authors and their works. We used as theoretical presuppositions studies on the Lexicon, Stylistics, Corpus Linguistics and Corpus Stylistics, having Corpus Linguistics as methodology. Among our references, we use Abbade (2011), Barbosa (1991), Berber Sardinha (1999, 2000, 2009), Biderman (1978, 1987, 2001), Finatto (2011), Fromm (2003), Mahlberg (2020), Martins (2012), Shepherd (2012, 2013, 2019) and Tagnin (2018). Our corpora of study were composed by Paulo Coelho's literary novels, one of the most read authors today, as well as famous works by several Brazilian writers, produced at different times and various literary schools. The use of such corpora made it possible to verify the lexical style of Paulo Coelho, in aspects such as textual accessibility, textual complexity, lexical diversity, keywords, lexical and semantic fields and the use of hapax legomena. We also compared the lexical density and textual complexity of The Alchemist, by Paulo Coelho, establishing parallels with the works of other authors. For the proposal, we collected and assembled the corpora that included text digitalization, downloads, conversions, conferences and corrections. Then, we performed the analysis using tools such as WordSmith Tools 6.0 program (SCOTT, 2012) by the WordList, KeyWord and Concord tools; and by the Flesch index. The results allowed us to elaborate the methodological proposal for the analysis of literary works through Corpus Linguistics, and also analysis of stylistic and lexical aspects of Paulo Coelho's literary novels.